Targeting Emerging RNA Viruses by Engineered Human Superantibody to Hepatitis C Virus RNA-Dependent RNA Polymerase - Glab-ampai, Kittirat; Kaewchim, Kanasap; Thavorasak, Techit; Saenlom, Thanatsaran; Thepsawat, Watayagorn; Mahasongkram, Kodchakorn; Thueng-In, Kanyarat; Sookrung, Nitat; Chaicumpa, Wanpen; Chulanetra, Monrat (Frontiers in Microbiology, 2022)
RNA dependent RNA polymerase (RdRp) is a unique and highly conserved enzyme across all members of the RNA virus superfamilies. Besides, human does not have homolog of this protein. Therefore, the RdRp is an attractive target for a broadly effective therapeutic agent against the RNA viruses. In this study, a formerly generated cell-penetrating human single-chain antibody variable fragment (superantibody) to a conformational epitope of hepatitis C virus (HCV) RdRp that inhibited the polymerase activity leading to the HCV replication inhibition and the host innate immunity restoration, was tested against emerging/reemerging RNA viruses. The superantibody could inhibit replication of the other members of the Flaviviridae (DENV serotypes 1-4, ZIKV and JEV), Picornaviridae (genus Enterovirus: EV71, CVA16), and Coronaviridae (genus Alphacoronavirus: PEDV, and genus Betatacoronavirus: SARS-CoV-2 (Wuhan wild type and the variants of concern), in a dose-dependent manner, as demonstrated by reduction of intracellular viral RNAs and numbers of the released infectious particles. Computerized simulation indicated that the superantibody formed contact interfaces with many residues at the back of thumb domain (thumb II site, T2) of DENV, ZIKV, JEV, EV71 and CVA16 and fingers and thumb domains of the HCV and coronaviruses (PEDV and SARS-CoV-2). The superantibody binding may cause allosteric change of the spatial conformation of the enzyme and disrupt the catalytic activity leading to replication inhibition. Although the speculated molecular mechanism of the superantibody needs experimental support, existing data indicate that the superantibody has high potential as a non-chemical broadly effective anti-positive sense-RNA virus agent.